Anomia COVID-19. Próba identyfikacji zjawiska - Zdun, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Anomie is associated with transitional periods, and in particular with rapid change processes. The aftermath of a disaster or a calamity, including epidemics, can serve as one example of such changes.The spread of the disease not only puts to test financial security, but also brings about the axionormative redevelopment of the society. And eventually it also raises questions about the feasibility of axiological orders and axiological superiority in such situations. The contemporary context where anomie is emergent is the COVID pandemic. A full evaluation of this phenomenon requires a longterm approach. Ex ante analyses should focus on developing accurate evaluation tools, which is the research objective of this article.